An observational study on the clinical features of esophageal cancer followed by multiple primary cancers. (27th November 2018) - Hu, Zhipeng; Zhang, Min; Wang, Zhiwei; Song, Junlong; Jiang, Wanli; Li, Luocheng; Hu, Xiaoping
Aim: To investigate the nature of multiple primary cancers initiated by esophageal cancer-multiple primary cancers (EC-MPC).Patients & methods: SEER data about patients'/tumor characteristics, and survival were analyzed and compared.Results & conclusion: 1727 of 29, 733 registered EC patients have EC-MPC. Individuals diagnosed at 60–79 years old, earlier stage and/or moderately differentiated EC were more likely to get EC-MPC. Fewer patients in the EC-MPC group suffered from metastases. Patients in the EC-MPC group showed a longer survival rate and lower EC-specific deaths. Other factors like age, sex, race, tumor differentiation and Tumor, Node, Metastasis stage also affected survival. Radiation can improve survival. EC-MPC patients have some distinct features compared with solitary EC.